Enhancing 3G ETA solar cells with novel Bi2Se3 nanoparticles synthesized on TiO2: Impact of immersion cycles on PEC performance - Vijay S. Baviskar; Chandradip D. Jadhav; Deepak B. Salunkhe; Narayan M. Narkhede; Girish P. Patil (Next Energy, 2025)
The development of unexposed layer heterostructures by integrating metal chalcogenide semiconductors with metal oxide arrays offers a promising approach to enhance surface area, expand optical response, and improve charge kinetics key factors for achieving high-performance photoconversion devices. In this study, we introduce a facile, room-temperature chemical method using successive ionic layer adsorption and reaction (SILAR) to deposit Bi2Se3 nanoparticles onto spin-coated TiO2 arrays. We systematically explore the structural, optical, and surface morphological properties of the resulting TiO2/Bi2Se3 heterostructures. Our findings reveal that the thin layer of Bi2Se3 nanoparticles uniformly coats the porous TiO2, extending its optical response into the visible region. We also examine the charge kinetics and solar cell performance of devices constructed with an fluorine doped tin oxide (FTO)/TiO2/Bi2Se3/polysulfide/carbon-coated FTO sandwich-type architecture. Through comparative analysis, we assess the initial characterizations, charge kinetics, and photovoltaic performance of the TiO2/Bi2Se3 heterostructures across different SILAR cycles. Our results demonstrate a significant enhancement in photocurrent for the bilayer TiO2/Bi2Se3 architecture (0.55 mA/cm²) compared to bare TiO2 (0.041 mA/cm²). This research highlights the potential of the proposed heterostructure to improve the efficiency of energy conversion devices.